Identifying Levels of Engagement in Local Food Systems by Generation in the State of Georgia, U.S.A. - Abraham Tidwell; Alexa J Lamm (Journal of Applied Communications, 2020)
Local food systems are an emerging way for communities to build vibrant economies, improve health outcomes, and limit their environmental impact. Studies have shown local food engagement differs significantly between generations; however, what remains unclear is how generations’ perceptions and engagement compare to each other so the agricultural community can most effectively communicate about local food systems. Leveraging audience segmentation theory from social marketing, this study sought to address how the five living generations in the United States – Generation Z, Millennials, Generation X, Baby Boomers, and The Silent Generation – perceived and engaged with local food systems. To address this question, a non-probability opt-in sampling of 863 adults in the state of Georgia was used. Each participant was asked four questions pertaining to different aspects of local food systems – the purchase of local foods from grocery stores, use of local food markets, participation in local food events, and level of engagement with local food related media. Millennials and Generation X’ers expressed significantly higher levels of engagement with local food systems when compared to Baby Boomers and The Silent Generation, this was not observed between Generation Z and any other group. While Millennials and X’ers engaged at higher levels, significant opportunities remain for engagement through generation-specific media to turn the universal tepid interest in local food systems into action. Future research should seek to identify the relationship between generational media preferences and how effective they are at transforming interest in local food systems into action.
Keywords: local food systems; social marketing; generational differences; audience segmentation